Pendekatan Kajian Alquran dalam Tafsir: Perspektif Linguistik Bahasa Arab - Arief Satria Budhi (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2025)
Quranic studies through exegesis have become a rich and dynamic field, with the linguistic approach to the Arabic language playing a crucial role in understanding the meanings of its sacred verses. This article explores how linguistic analysis helps uncover the semantic, syntactic, and pragmatic dimensions of the Quranic text. By employing modern linguistic theories, such as discourse analysis, historical semantics, and Arabic morphology, this study highlights how an understanding of Arabic language structures can enrich Quranic interpretation. The primary focus of this research is to elucidate the relationship between literal and contextual meanings of the verses and how linguistic elements support interpretations relevant to contemporary Muslim needs. The findings reveal that a linguistic approach not only deepens the understanding of the Quran but also provides a framework for bridging classical and modern exegesis. Thus, this article contributes to the development of a linguistically-based Quranic exegesis methodology that addresses the challenges of the present era.